John Wesley's teachings - Oden, Thomas C.; Oden, Thomas C. (Grand Rapids, MI : Zondervan, 2012)
"Wesley was a prolific writer and commentator on Scripture, yet it is commonly held that he was not systematic or internally consistent in his theology and doctrinal teachings. On the contrary, Thomas C. Oden intends to demonstrate here that Wesley displayed a remarkable degree of consistency over sixty years of preaching and ministry. The book helps readers to grasp Wesley's essential teachings in an accessible form so that the person desiring to go directly to Wesley's own writings (which fill eighteen volumes) will know exactly where to turn."--Publisher's description.
V. 1. God and providence -- v. 2. Christ and salvation -- v. 3. The practice of pastoral care -- v. 4. Issues of ethics and society.
Revised edition of: John Wesley's scriptural Christianity. c1994.
Includes bibliographical references and indexes.
Keywords: Wesley, John, -- 1703-1791.; Theology, Doctrinal; Methodist Church -- Doctrines; Theology, Doctrinal -- History -- 18th century; Methodist Church -- Doctrines -- History -- 18th century; History